(untitled) (Revista de Estudos da Linguagem, 2024)
This article emphasizes on the analysis of the phenomenon of palatalization of the /t/ and /d/ segments in syllabic onset contiguous to diphthong, in Mossoró–RN. The postulations by Clements and Hume (1996) on Feature Geometry, by Selkirk (1982) on the Autosegmental Syllable Model form the theoretical basis of the research, which transversally has also brought to the discussion sociocultural characteristics of the speakers (ARAGÃO, 2006, 2020; CARDOSO; MOTA; PAIM, 2012; WEINREICH; LABOV; HERZOG, 2006). The data collection methodology has involved two Playful Phonetic-Phonological Questionnaires, a Phonetic-Phonological Questionnaire and a Semi-Directed Narrative applied to six informants. The extra-linguistic variables considered are sex, age and education. After the field research, the data were recorded in hearing phonetic transcription and some of them underwent acoustic analysis. The research aims to verify the motivations for palatalization in this community, until then known as non-palatalizing. Results have indicated that palatalization is linguistically significant in Mossoró, especially in the context of /t/ and /d/ in onset sharing final unstressed syllable of word with diphthong beginning with [i] or [j]. Furthermore, the following interpretation is proposed: palatalization has occurd by spreading the /i/ Vowel node and the affrication by spreading of that node and [+continuous], branched from the Root node. Finally, the analysis has revealed that there is evidence of more frequent palatalization on the part of women and the younger ones – when taking the extralinguistic scope into account.